THE RESEARCH OF EFFECTIVENESS OF THE PEDAGOGICAL CONDITIONS OF THE FORMATION OF FUTURE TECHNOLOGISTS' READINESS FOR AN INNOVATIONAL ACTIVITY AT COLLEGES OF AGRICULTURAL PROFILE - Валентина Кобзар (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
This article presents the analysis of the current stage, which the investigation of the problem of the formation of future technologists' readiness for innovation and definition of its structural components are on. The research outlines the author's position concerning the components (motivational, cognitive and content, search and creative), and levels of formation (low, medium, high) of future technologists' readiness for innovative activity at agricultural colleges. There has been graphically presented the analysis of the levels of the mentioned above readiness formation according to each of the components. The introduced methods have been experimentally proved to be effective and perspective.